Vitamin D: Marker or Mechanism of Action? - Jacobs, Elizabeth T. (2011)
The field of vitamin D and cancer research has been moving forward quickly. However, some challenges remain regarding the interpretation and integration of data collected from epidemiological investigations and laboratory experiments. These include consideration of vitamin D biology, a better understanding of characteristics that affect concentrations of the biomarker of vitamin D status, 25(OH)D, and elucidation of variation in response to vitamin D supplementation. To further the field of vitamin D and cancer prevention, future studies will need to bridge the gap between the epidemiology and molecular biology of vitamin D activity in carcinogenesis.